Enhanced interleukin activity following asbestos inhalation. - Hartmann, D P (1984)
Asbestos inhalation can cause pulmonary fibrosis and is associated with a variety of immunological abnormalities. The purpose of this study was to evaluate the effects of asbestos inhalation on interleukin-1 (IL-1) and interleukin-2 (IL-2) production in a rodent model. Two groups of rats were exposed, by intermittent inhalation, to either amphibole (crocidolite) or serpentine (chrysotile) asbestos. A third (control) group of rats was sham exposed to clean air. Animals from the three exposure groups were thereafter immunized (or not immunized) with fetal calf serum antigens. In order to assay interleukin activity, supernatants were generated from cultures containing alveolar macrophages and autologous splenic lymphocytes, and from cultures containing alveolar macrophages alone. Using assay systems designed to detect IL-1 and IL-2 functional activity, the supernatants were evaluated for their capacity to stimulate lymphoproliferation and fibroblast DNA synthesis. Macrophage-lymphocyte co-culture supernatants, when obtained from immunized, asbestos exposed rats, contained greater IL-1 and IL-2 activity than identical supernatants from immunized, sham exposed animals. These between group differences were not, however, observed in supernatants from unimmunized rats, or when supernatants were generated in the absence of immune lymphocytes. These observations suggest that asbestos exposure is associated with enhanced activation of lymphocytes by antigens. The possible relevance of these findings to asbestos related fibrogenesis and immunological stimulation is discussed.